Effects of Visual Gaming and Motives on Health Hazards Among Adolescents Living in the Southeastern Part of Bangladesh - Arabi, Shakila; Jahan, Sadia Tasnuva (International Journal of Human and Health Sciences (IJHHS), 2026)
Online gaming has become a dominant form of entertainment among adolescents, especially in urban areas of developing countries like Bangladesh. While gaming offers opportunities for emotional relief and social engagement, excessive use has raised public health concerns, particularly regarding its impact on adolescents’ mental and physical well-being. A cross-sectional study was conducted between July and December of 2024 among adolescents (aged 13–18 years) living in Chattogram, a southeastern city of Bangladesh, to explore the association between online gaming habits and the prevalence of depressive symptoms, musculoskeletal discomfort, psychosomatic complaints. Using a convenience sampling method, a total of 373 students (from two institutions – Islamia College and Govt. City College) were selected. Data was collected through a pre-tested, semi-structured questionnaire. Among 373 adolescents, 172(46.1%) were male and 201(53.9%) were female. Male-female ratio was 1:1.17. Most of the participants were 17 years old (52.3%), followed by 18 years old (22.8%). Only 8.3% of respondents reported depressive symptoms. 81.5% of adolescents reported musculoskeletal discomfort. 58.2% experienced psychosomatic complaints (e.g., headaches, fatigue, sleep disturbances). 43.4% reported issues in their social relationships. Age was not a significant factor for depression and psychosomatic symptoms (p>0.05), but associated with musculoskeletal symptoms (p<0.05). Gender, gaming type, gaming duration, gaming frequency were found significant with depression, psychosomatic and musculoskeletal symptoms (p<0.001). However, gaming motivation was significantly associated with depression (p<0.001) and psychosomatic symptoms (p<0.05), except with musculoskeletal symptoms (p>0.05). Moreover, significant association was observed between social relationships and sociodemographic and behavioral variables among adolescents (p<0.001) The results may inform future strategies for promoting healthier gaming habits and supporting adolescent well-being in similar urban settings. International Journal of Human and Health Sciences Vol. 10 No. 02 Apr’26 Page: 122-127